1998
DOI: 10.1038/bjc.1998.326
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of MVP (mitomycin-C, vinblastine and cisplatin) chemotherapy in small-cell lung cancer

Abstract: Summary MVP chemotherapy (mitomycin C 8 mgm-2, courses 1,2,4 and 6, vinblastine 6 mgm-2, cisplatin 50 mgm-2) is an active low-toxicity regimen in non-small-cell lung cancer (NSCLC). Based on the single-agent activity of these agents in SCLC, we have conducted a phase 11 trial of MVP in SCLC. Fifty chemo-naive patients with SCLC were entered in this trial. There were 33 men and 17 women with median age 66 years (range 46-83 years); 18 patients had limited disease (LD) and 32 extensive disease (ED). WHO performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The remaining 314 records dealt with the LC13; however, of these, 74 records were excluded because they did not present original data obtained by means of the module. Consequently, n = 240 articles were considered clinical studies according to our definition and were included in further analyses …”
Section: Resultsmentioning
confidence: 99%
“…The remaining 314 records dealt with the LC13; however, of these, 74 records were excluded because they did not present original data obtained by means of the module. Consequently, n = 240 articles were considered clinical studies according to our definition and were included in further analyses …”
Section: Resultsmentioning
confidence: 99%
“…123 Other studies which have included patients with a median age of >65 years have shown a favourable response and survival data together with the suggestion of improved symptom control, less hospitalisation, and reduced risks of life threatening sepsis. [124][125][126][127] Most recently, the cisplatin-irinotecan combination has been shown to be more efficacious in extensive stage disease than cisplatinetoposide, and this effect persisted despite adjustment for age (up to 70 years) and performance status. 128 Early reports of newer combinations are also emerging with encouraging response rates in phase II studies.…”
Section: Treatment Strategies For Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%
“…Our present survival figures (1993-1998 group) reflect our day-to-day practice, yet compare favourably with those reported in the current medical literature, both with conventional and novel therapies (Table 3). [7][8][9][10] In patients with SCLC, median survival continues to improve but improvement in longterm survival remains an elusive goal. More intensive chemotherapy regimes have shown improved survival, but are limited by excessive toxicity.…”
Section: Patientsmentioning
confidence: 99%